Analisis Faktor-Faktor yang Mempengaruhi Pertumbuhan Laba Pada Bank Umum Syariah - Fitriyanti Fitriyanti; Deky Anwar; Sri Delasmi Jayanti (Jurnal Terapan Ilmu Ekonomi, Manajemen dan Bisnis, 2022)
This study aims to determine the effect of Third Party Funds (TPF), Total Asset Turnover (TATO), and Financing to Deposit Ratio (FDR) on profit growth in Islamic Commercial Banks. The sample of this research is Islamic Commercial Banks registered with the Financial Services Authority in 2015-2019. The sample selection used purposive sampling in order to obtain as many as 10 banks. The multiple regression analysis model of panel data shows that partially TPF has a positive and significant effect on profit growth. TATO has no effect on profit growth, FDR has no effect on profit growth and simultaneously TPF, TATO, and FDR have an effect on profit growth. Â